PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN KEPEMIMPINAN TRANSFORMASIONAL PADA KINERJA GURU SMK NEGERI 3 WONOSARI - , Yoce Febrianus Abidano ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discusses the influence of transactional and transformational leadership behavior on teacher performance SMK Negeri 3 Wonosari. In connection with the matter to be investigated, proposed the following hypothesis: (1) The effect transactional leadership on teacher performance. (2) The effect of transformational leadership on teacher performance. That aims to examine and analyze the effect of transactional leadership and transformational leadership on teacher performance. The population in this study were all teachers as SMK Negeri Gunung Kidul. The sampling technique used is the sampling convenience at SMK Negeri 3 Wonosari which amounts to 75 civil servants and non-civil servant teachers. Transactional leadership style and transformational leadership style using multifactor Leadership Questionnaire (MLQ) models item of Bass and Avolio (2004) and the performance model of the item using the Teacher Performance Criteria Questionnaire (TPCQ) Cheffers theory and Sullivan (2000). Primary data collection using questionnaires. Test data analysis using multiple linear regression analysis with SPSS 20. Test results showed (1) leadership transactional positive but not significant effect on the performance of teachers. The level of transactional leadership has no effect on teacher performance and more emphasis on contingent dimensions, (2) transformational leadership and significant positive effect on teacher performance. The greater role of principal transformational leadership, the greater the performance of teachers. The conclusion transactional leadership style is not supported and transformational leadership style is supported on teacher performance. Transformational leadership style dominant influence on teacher performance. The recommended advice is to apply principal transformational leadership, transactional leadership is also necessary though. But transformational leadership proved dominant effect on performance. And for future research could add another variable.